Residents’ assessment for vertical housing complexes in Al-Hilla Case study: Hilla/1, Hilla/2, complexes - QAHTAN OMRAN, AWS; B. Motlak, Jamal (Journal of Planner and Development, 2024)
Abstract: Housing have a significant impact on both the environment and people's quality of life, it refers to the design, construction, and operation of residential buildings that minimize their environmental impact while providing healthy, comfortable, and affordable homes for people, assessing the citizens' dissatisfaction with housing in vertical residential complexes, the quality of residential complexes based on services not unit details,Two residential complexes locate, one of these complexes has a larger housing area than the other. A questionnaire of 28 questions, were collected physically from the residents in these building. The results illustrate a positive response were good by 25%, and moderate by 25%, and 30% insufficient for adequacy of social services and 34% for services provided. However, the other responses were negative with higher percentage (58%). Furthermore, these positive responses were from the residents who live in the complex, which has a large area, the resident’s assessment better towards the complex offering more services although the flat area was smaller.